2005
DOI: 10.1002/dvdy.20343
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation in the developing lateral line system of zebrafish embryos

Abstract: The sensory organs of the embryonic lateral line system are deposited by migrating primordia that originate in the otic region. Here, we examine the pattern of cell proliferation in the posterior lateral line system. We conclude that three phases of cell proliferation are involved in the generation of this system, separated by two phases of mitotic quiescence. The first phase corresponds to generalized proliferation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 19 publications
6
43
0
Order By: Relevance
“…It has previously been noted that the progenitor cells of the primary primordium, primI, enter a phase of mitotic quiescence around 10 hpf and do not resume proliferation until 16 -18 hpf (Laguerre et al, 2005). These authors also noted that, whereas exposure to bromodeoxyuridine between 8 and 10 hpf labels most PLL neurons, exposure starting at 10 hpf labels only a few neurons, refining a previous finding that PLL neurons become postmitotic at some time between 8 and 13 hpf (Metcalfe, 1983).…”
Section: Discussionsupporting
confidence: 52%
“…It has previously been noted that the progenitor cells of the primary primordium, primI, enter a phase of mitotic quiescence around 10 hpf and do not resume proliferation until 16 -18 hpf (Laguerre et al, 2005). These authors also noted that, whereas exposure to bromodeoxyuridine between 8 and 10 hpf labels most PLL neurons, exposure starting at 10 hpf labels only a few neurons, refining a previous finding that PLL neurons become postmitotic at some time between 8 and 13 hpf (Metcalfe, 1983).…”
Section: Discussionsupporting
confidence: 52%
“…Finally, we observed that the sox3-expressing p4 subdomain migrates posteriorly from its original domain along the body axis after the 20-somite stage (data not shown). Given that this migration trend of the p4 subdomain is similar to that of the posterior lateral line primordium, as revealed by morphological observation (Laguerre et al, 2005) and expression of the chemokine receptor cxcr4 (Chong et al, 2001;David et al, 2002), we suggest that the p4 subdomain represents the anlage of the posterior lateral line system.…”
Section: Early Development Of the Epibranchial Placode In Zebrafishsupporting
confidence: 56%
“…We found that lef1 activity is required for the wave of cell proliferation that takes place in the PLL placode before the onset of migration, after a long period of quiescence extending from around 10 hpf to around 18 hpf (Laguerre et al, 2005). This early burst of DNA replication is Error bars indicate standard deviations, n ¼ 31 for the control, 27 for the morphants (5 lef1-MO injected embryos showed no phenotype at 3 days postfertilization [dpf] and were not included in the calculations).…”
Section: Discussionmentioning
confidence: 86%
“…Contrary to this early burst, DNA replication is asymmetrically distributed in the migrating primordium, with leading cells showing BrdU incorporation at a constant rate, whereas incorporation in the trailing cells only occurs in phasic pulses synchronized with events of neuromast deposition (Laguerre et al, 2005). It seems conceivable that, much like ubiquitous lef1 activity is required for ubiquitous proliferation in the presumptive tissue, Wnt signaling acting through lef1 is responsible for the continuous DNA replicating activity in the leading cells of the migrating primordium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation